Macrophage Plasma Membrane Cholesterol Contributes to Brucella abortus Infection of Mice - Watarai, Masahisa (American Society for Microbiology, 2002)
Brucella abortus is a facultative intracellular bacterium capable of surviving inside macrophages. Intracellular replication of B. abortus requires the VirB complex, which is highly similar to conjugative DNA transfer systems. In this study, we show that plasma membrane cholesterol of macrophages is required for the VirB-dependent internalization of B. abortus and also contributes to the establishment of bacterial infection in mice. The internalization of B. abortus was accelerated by treating macrophages with acetylated low-density lipoprotein (acLDL). Treatment of acyl coenzyme A:cholesterol acyltransferase inhibitor, HL-004, to macrophages preloaded with acLDL accelerated the internalization of B. abortus. Ketoconazole, which inhibits cholesterol transport from lysosomes to the cell surface, inhibited the internalization and intracellular replication of B. abortus in macrophages. The Niemann-Pick C1 gene (NPC1), the gene for Niemann-Pick type C disease, characterized by an accumulation of cholesterol in most tissues, promoted B. abortus infection. NPC1-deficient mice were resistant to the bacterial infection. Molecules associated with cholesterol-rich microdomains, “lipid rafts,” accumulate in intracellular vesicles of macrophages isolated from NPC1-deficient mice, and the macrophages yielded no intracellular replication of B. abortus. Thus, trafficking of cholesterol-associated microdomains controlled by NPC1 is critical for the establishment of B. abortus infection.